Engineering Mechanics , Statics - J.L Meriam (Wiley, 2001)
This concise and authoritative book emphasizes basic principles and problem formulation. It illustrates both the cohesiveness of the relatively few fundamental ideas in this area and the great variety of problems these ideas solve. All of the problems address principles and procedures inherent in the design and analysis of engineering structures and mechanical systems, with many of the problems referring explicitly to design considerations. --This text refers to an out of print or unavailable edition of this title.